Governance Turbulance: An Analysis of the Ex-Lion Air Recruitment Controversy at Garuda Indonesia and its Implications for Corporate Governance and Reputational Risk Management - Rizki Agung Ramadani; Tiyanda Hanti Arum Kusuma (CV. ULIL ALBAB CORP, 2025)
This study aims to analyze in depth the controversy surrounding the recruitment of former Lion Air employees at PT Garuda Indonesia (Persero) Tbk and its implications for corporate governance principles (Good Corporate Governance/GCG) and risk management frameworks, particularly reputation risk. Adopting a descriptive qualitative approach with a single case study at PT Garuda Indonesia (Persero) Tbk, this research uses the decision to recruit 14 former Lion Air employees during the 2024-2025 period as the unit of analysis. Data was collected through documentary studies, including news reports from reputable media outlets, official company statements, and labor union publications. Data was analyzed using qualitative content analysis, comparing narratives from various stakeholders (management vs. labor unions) and evaluating their alignment with GCG theory (Transparency, Accountability, Responsibility, Independence, Fairness) and the risk management framework (COSO ERM). Data triangulation was conducted by comparing information from various sources to ensure the validity of the findings. The findings indicate that this recruitment controversy triggered significant internal tensions, a decline in public trust and stock value, and raised serious questions about compliance with the principles of independence and transparency in GCG. Although management claimed that the recruitment process was in accordance with procedures and GCG principles, perceptions of conflicts of interest due to the CEO's background and a lack of transparent communication were the primary triggers of the reputational crisis.